Digital Diabetes Congress 2019. (September 2019) - Han, Julia; King, Fraya; Klonoff, David; Drincic, Andjela; Crosby, Keesha Perkins; Robinson, Thomas; Gabbay, Robert A.; Oley, Leslie; Ahn, David; Evans, Bill; Salber, Patricia; Cruz, Marisa; et al.
New applications of digital health software and sensors for diabetes are rapidly becoming available. The link between healthcare, wearable or carryable devices, and the use of smartphones is increasingly being used by patients for timely information and by healthcare professionals to deliver information and personalized advice and to encourage healthy behavior. To assemble stakeholders from academia, industry, and government, Diabetes Technology Society and Sansum Diabetes Research Institute hosted the 3rd Annual Digital Diabetes Congress on May 14-15, 2019 in San Francisco. Physicians, entrepreneurs, attorneys, psychologists, and other leaders in the diabetes technology field came together to discuss current and future trends and applications of digital tools in diabetes. The meeting focused on eight topics: 1) User Interface/User Experience (UI/UX) for Digital Health, 2) clinical aspects, 3) marketing, 4) investment, 5) regulation, 6) who owns the data, 7) engagement, and 8) the future of digital health. This meeting report contains summaries of the meeting's eight plenary sessions and eight panel discussions, which were all focused on an important aspect of the development, use, and regulation of diabetes digital tools.